COMPARING PRICES OF COMMONLY USED GASTRIC ACID SUPPRESSANTS AVAILABLE IN INDIA - Nerlekar, Sharmada; Rashmi, Abhilasha; Karia, Sagar; Desousa, Avinash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Drugs to reduce gastric acid secretion are one of the commonly prescribed drugs by doctors of varied branches. There are many numbers of brands of different drugs available in India. Hence, this study was designed to compare the prices of different gastric acid suppressants of various brands available in India. Methods: The Current Index of Medical Specialities October 2015-January 2016 was used to analyze the prices of various gastric acid suppressants and their combinations. The cost of each molecule of different strengths was tabulated and cost range and % price variation were calculated. Results: A wide range of cost variations were seen among different categories of gastric acid suppressants available more so among proton pump inhibitors. Furthermore, it was observed that wide variety of fixed drug combinations is available. Conclusion: Price control mechanism has an important role and is very much important to reduce the cost burden of treatment particularly in India. Keywords: Comparison, Gastric acid suppressants, India, Brands, Current Index of Medical Specialities.